Expression of DAZL and BOULE in Spermatogenic Failure of Infertile Men: A Study - Silvia Werdhy Lestari (Journal of Global Pharma Technology, 2016)
DAZ-like (DAZL) on chromosome 3 and BOULE on chromosome 2 are genes included in the DAZ gene family. These genes have a role as regulator of specific cell cycle in germ cells. Mutations on DAZ gene family cause meiotic arrest and infertility. DAZL and BOULE are known to have interaction with CDC25 in regulating meiosis in the cell cycle. The examination of infertility on azoospermia cases, which are caused by spermatogenesis arrest, has so far been limited by histological examination from testicular biopsy. Therefore, molecular research is needed to determine the candidate genes that could be used as a marker in improving the quality of testicular biopsy examination. This research is a cross-sectional study which used 40 biopsy testes samples based on Johnsen scores 2 to 8. The mRNA expression analysis of DAZL and BOULE used qRT-PCR. The DAZL gene began to be expressed in scoring 5-8, where there was an increase from scoring 5-7 then a decrease in scoring 8. The BOULE gene began to be expressed in scoring 2 – 8, but there was an increase from scoring 4 – 7 and then a decrease in scoring 6 and 8. The correlation between the mRNA expressions of DAZL and BOULE showed a significant positive correlation (r = 0.415, p<0.05). These results indicated that both DAZL and Boule contribute in the failure of spermatogenesis.Keywords: Male infertility, Spermatogenic failure, Johnson score, DAZL, BOULE